(untitled) (CAHIERS MAGELLANES-NS, 2024)
Breast cancer is modern day burden in women, in breast cancer prognosis and treatment always chromosomal instability is associated. Breast cancer persists as one of the most widespread malignancies globally, presenting substantial hurdles in diagnosis and treatment. On chromosome 17, HER2 oncogene is located. It is always associated with breast cancers in 20% of cases. This study conducted to find the correlation between molecular subtypes and histologic classifications of breast cancer, shedding light on how these subtypes influence tumor appearances in imaging studies. Methods: This was a both retrospective and prospective study. The representative tumor area was identified and marked by diamond pencil over the under surface of the slide. A further section is taken again from the same blocks on Poly L lysin coated slides for the Fluorescence in situ hybridization (FISH). Signals were observed and and quantified. Signals were counted by two investigators independently. The amplification index was calculated as the ratio of c-MYC, HER2/neu signals to chromosome 8,17 centromere signals. A 2.2-fold increase served as the criterion to determine the presence of the amplification of c-Myc, HER2/neu polysomy of CEP8, CEP17. Results: CEP8 polysomy was found 26.6%, CEP17 polysomy was found in 20% of the IDC cases and CEP8 polysomy was found in 26.6%, CEP17 polysomy found in 33.3% of the DCIS with microinvasion cases respectively. whereas polysomy was significantly more frequent in IDC compared with DCIS cases samples (p=0.00000]. DCIS cells showed 93.3% disomy. 6.6% of the cells showed monosomy. Conclusion: These findings suggest that polysomy of CEP8, CEP17 more frequently observed in IDC and that disomy is more common in tissue of DCIS. Mitotic activity corresponding with the polysomy of CEP8, CEP17.